The Influence of Own Capital and Business Location on The Income of Micro Small and Medium Enterprises (MSMEs) - Syafii, Mochamad; Jamilah, Dziyl Waslatiyl; Rusdiyanto, Rusdiyanto (Indonesian Journal of Social Science Research, 2024)
The purpose of this study is to investigate and demonstrate how own capital and business location affect the revenue of micro, small, and medium-sized businesses in the Gresik Regency. Entrepreneurs need to know if their own capital and business location have a positive and significant impact on the income they will receive in the future, which is why this research is crucial. With 69 respondents in all, samples were gathered for this quantitative approach study. Both observations and questionnaires were used in the data collection process. The Slovin calculation formula and random sample procedures were used in this study. A Likert scale is used in data analysis with Google Form media. Multiple linear regression and hypothesis testing are the methods of analysis used. The study's findings demonstrate that own capital and company location have a demonstrable positive and significant impact on MSMEs' revenue in the Gresik Regency.